2018
DOI: 10.1007/s10964-018-0916-4
|View full text |Cite
|
Sign up to set email alerts
|

Burdened or Efficacious? Subgroups of Chinese American Language Brokers, Predictors, and Long-Term Outcomes

Abstract: Despite growing research on youth language brokering in immigrant families, evidence regarding its developmental outcomes remains mixed. This study took a person-centered approach, exploring subgroups of language brokers and identifying predictors and long-term outcomes of the subgroup membership. Participants were Chinese American adolescents (N = 350 at Time 1; M = 17.04; SD = 0.72; 59% female) followed over two waves spaced four years apart (longitudinal N = 291). Two distinct subgroups of adolescent langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
(56 reference statements)
2
20
0
2
Order By: Relevance
“…These findings point to the importance of how the negative subjective experience of the language broker in situ may relate to poor psychological outcomes. Our findings are similar to the work of Shen et al (2019) who found that brokers who felt burdened and continued to feel burdened reported greater parental relationship problems and psychosocial problems in emerging adulthood. Likewise, Weisskirch (2013) also found that burden when LB predicted self-esteem and self-efficacy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These findings point to the importance of how the negative subjective experience of the language broker in situ may relate to poor psychological outcomes. Our findings are similar to the work of Shen et al (2019) who found that brokers who felt burdened and continued to feel burdened reported greater parental relationship problems and psychosocial problems in emerging adulthood. Likewise, Weisskirch (2013) also found that burden when LB predicted self-esteem and self-efficacy.…”
Section: Discussionsupporting
confidence: 89%
“…Those with insecure attachments are likely to perceive LB as more problematic than those with secure attachments. Since the literature has supported the link between frequency and perceptions of LB and psychological outcomes (e.g., Shen, et al, 2019; Rainey et al, 2014), it is likely that the relationship of attachment to measures of psychological well-being is indirectly affected by frequency and perceptions of LB. We hypothesize that the relationship between attachment and psychological well-being will be mediated by frequency and perceptions of LB.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that Latino language brokers who often translate in high-stakes contexts (i.e., stressful situations that require accurate translation; e.g., medical or legal documents) exhibit negative psychological outcomes, but those that frequently translate in low-stakes (e.g., at a restaurant) or everyday (e.g., notes from the school) contexts do not (Anguiano, 2018). Similarly, another recent study found that Chinese American adolescents who feel efficacious about brokering in adolescence exhibit fewer psychological and behavioral adjustment problems in emerging adulthood relative to those that are stressed and burdened about brokering, regardless of how often they engaged in language brokering (Shen, Kim, & Benner, 2019). Therefore, whereas language brokering stress is associated with developmental costs, providing frequent language brokering per se does not necessarily jeopardize adolescents' psychological and behavioral well-being and can even confer developmental benefits when adolescents do not perceive the practice as stressful.…”
Section: Discussionmentioning
confidence: 99%